A legal analysis of South Africa’s stance on capital punishment in relation to Botswana, Nigeria, and international conventions - Mashigo, Itumeleng (The IIE, 2022)
In the beginning of 2022, the police minister, Bheki Cele addressed the nation on the crime statistics that were collected during 2021/2022 financial year. In his presentation, he disclosed figures that would send chills down the spines of the South Africans. Regarding murder, it was exclaimed that in a period between July 2021 and September 2021, the number of murders committed in the Republic was more than 6000 which represents an increase over the same time frame of the previous year. A similar trend can be observed for rape where by 9556 rapes were reported within the same July to September 2021 period which reflected an increase over the same time frame of the previous year. This trend is followed by other classes of offences which illustrate a general increase of unlawfulness in the country. This realisation sparks the thought of whether we have adopted inadequate measures to prevent crimes out of the dream of upholding constitutional values which may not be ideal for the wellbeing of the citizens of the Republic in the modern day. The call for there in statement of the death penalty can be heard throughout various facets of South African society. Political parties such as the IFP have called on more hard-line measures on dealing with crime which includes the reinstatement of capital punishment. Ordinary citizens have also taken a stance to see its reinstatement following the rape and murder of Uyinene Mrwetyana and other high-profile murders. “Should and/or can capital punishment be reinstated in modern day South Africa”? and if so “under what circumstances would it work”? That is what will be discussed and debated throughout this paper.
Keywords: South Africa; Capital punishment; International convention